Walisongo Da'wah Strategy: Analysis of the Symbolism of Amar Ma’ruf Nahi Munkar in Semar and Togog Characters - Hidayatullah, Ahmad (Munazzama: Journal of Islamic Management and Pilgrimage, 2021)
The Spreaders of Islam in the early period -Walisongo- used wayang (puppet), which is very thick with symbolic values as a media of da’wah, and two of those are in the character of Semar and Togog. Both Semar and Togog have a crucial position in Javanese Wayang's story, which are used as a strategy to make Islamic teachings reachable in society. By using a qualitative descriptive method, this study explores how the symbolic representation of amar ma’ruf nahi munkar in the construction of Semar and Togog characters. The result of this study that Semar as a guardian of protagonist character, such as Pandawa is a representation of amar ma’ruf. On the other side, Togog, the guardian of giants and other antagonist characters, is represented symbolically as nahi munkar. Nevertheless, the Togog’s position, which is in the part of antagonist does not make him automatically become an antagonist itself. He even has a more challenging and more glorious role than Semar because he must be in the dark circle without being a part of that dark itself.